Analisis Pengaruh Rasio-Rasio Keuangan Terhadap Rasio Beban Operasional-Pendapatan Operasional (BOPO) pada Bank Umum Syariah di Indonesia - Amri Darma Kurniawan S; Rusiadi Rusiadi; Bakhtiar Efendi; Lia Nazliana Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of Islamic banking financial ratios in the form of Return on Assets (ROA) Ratio, Non Performing Financing (NPF) Ratio, Financing to Deposit Ratio (FDR) and Total Asset Turnover (TATO) on the Operational Cost-Operational Income Ratio (BOPO) at Sharia Commercial Banks in Indonesia. This research uses a quantitative approach with sample data totaling 7 (seven) sharia commercial banks out of 13 (thirteen) sharia commercial bank populations registered with the Financial Services Authority. Research data uses secondary data for the annual period in the period 2010 - 2023. By using the ARDL (Autoreggressive Distributed Lag) panel model using the PMG (Pooled Mean Group) method, the research results show that in the panel, it turns out that the Leading Indicator is the effectiveness of the variable in controlling the BOPO Ratio at Sharia Commercial Banks in Indonesia is Return on Assets (ROA), where ROA significantly influences the BOPO Ratio at Bank Muamalat Indonesia, Bank Aceh Syariah, Bank Riau Kepri Syariah, Bank Jabar Banten Syariah, Bank Mega Syariah, and Bank NTB Syariah, with stable positions in the short and long term. Of the 7 (seven) Sharia Commercial Banks that are the objects of research, there are 4 (four) banks that are leading indicators of the effectiveness of sharia banking in influencing the stability of the BOPO ratio, namely: Bank Aceh Syariah, Bank Riau Kepri Syariah, Bank Jabar Banten Syariah, and Bank Mega Syariah through ROA, NPF, FDR, and TATO. Financing to Deposit Ratio (FDR) is also capable of being a Leading Indicator of variable effectiveness to influence the BOPO Ratio at Bank Muamalat Indonesia, Bank Aceh Syariah, Bank Riau Kepri Syariah, Bank BCA Syariah, Bank Jabar Banten Syariah, Bank Mega Syariah, and Bank NTB Syariah, However, its position is unstable in the short and long term.